2022
DOI: 10.1136/ejhpharm-2022-003535
|View full text |Cite
|
Sign up to set email alerts
|

Meropenem population pharmacokinetics and model-based dosing optimisation in patients with serious bacterial infection

Abstract: ObjectivesThe objective of this study was to develop a population pharmacokinetic model of meropenem in a heterogeneous population of patients with a serious bacterial infection in order to propose dosing optimisation leading to improved achievement of the pharmacokinetic/pharmacodynamic (PK/PD) target.MethodsA total of 174 meropenem serum levels obtained from 144 patients during therapeutic drug monitoring were analysed using a non-linear mixed-effects modelling approach and Monte Carlo simulation was then us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Although only a few studies have investigated the population pharmacokinetics of carbapenems in septic patients, an increase in the volume of distribution is common. Fukumoto et al revealed the volume of distribution of meropenem V (V 1 +V 2 ) in patients with sepsis was 39.7L (Fukumoto et al, 2023), while Murínová et al reported an average V of 55L in patients with serious infection (Murínová et al, 2022), respectively. Both studies reported higher V of meropenem in patients with sepsis comparing with other patients, which may be caused by the increase in V of hydrophilic drugs, which is quite common in critically ill patients (Roberts and Lipman, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although only a few studies have investigated the population pharmacokinetics of carbapenems in septic patients, an increase in the volume of distribution is common. Fukumoto et al revealed the volume of distribution of meropenem V (V 1 +V 2 ) in patients with sepsis was 39.7L (Fukumoto et al, 2023), while Murínová et al reported an average V of 55L in patients with serious infection (Murínová et al, 2022), respectively. Both studies reported higher V of meropenem in patients with sepsis comparing with other patients, which may be caused by the increase in V of hydrophilic drugs, which is quite common in critically ill patients (Roberts and Lipman, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Endotoxins induce the synthesis of various endogenous mediators, including cytokines, interleukins, and platelet-activating factor, can influence the vascular endothelium, leading to vasodilation, along with an aberrant distribution of blood flow, endothelial damage, and heightened capillary permeability. This syndrome results in fluid translocation from the intravascular compartment to the interstitial space, consequently increasing the Vd of water-soluble drugs, including carbapenems, and diminishing their serum concentrations (Murínová et al, 2022). It was reported that bipenem has a relatively short elimination half-life of approximately 1 hour.…”
Section: Introductionmentioning
confidence: 99%